Determinants of successful use of sirolimus in renal transplant patients - Naik, Marcel G.; Jürgensen, Jan Steffen; Arns, Wolfgang; Basic, Edin; Budde, Klemens; Eitner, Frank; Fischereder, Michael; Goßmann, Jan; Heller, Katharina M.; Heyne, Nils; Morath, Christian; Riester, Udo; et al. (Transplantation proceedings, 2020)
Background - Sirolimus is an established immunosuppressant in renal transplantation with antineoplastic and antiviral features, but side effects like proteinuria limit its use. The aim of this retrospective multicenter observational study is to define predictors for determining which patients most likely benefit from a sirolimus-based therapy. - Methods - All patients from 10 German centers that were switched to a sirolimus-containing maintenance immunosuppression in 2000 to 2008 after 3 months or later post-transplantation were enrolled (n = 726). Observation times after switching to sirolimus ranged from 4 days to 9 years (median: 24.3 months). With multinomial logistic regression, risk factors for the endpoints terminal graft failure and withdrawal of sirolimus therapy compared to successful therapy were identified. - Results - Successful sirolimus therapy was observed in 304 patients. Forty patients died with functioning graft. Therapy failures included graft loss (n = 106) and sirolimus-discontinuation for various reasons (n = 276). Successful sirolimus-use was predicted in 83% and graft failure in 65%, whereas prediction of deliberate sirolimus-discontinuation was poor (48%). Most favorable results for sirolimus-use were observed in patients switched in 2006 to 2008. Using ROC analysis, an estimated glomerular filtration rate (eGFR) below 32 mL/min was shown to be the cut-off in patients withdrawing from therapy as a result of renal reasons, as well as in patients with graft loss. Proteinuria above 151 mg/L was shown to be predictive for patients with graft failure. - Conclusions - eGFR and proteinuria are the major determinants for successful sirolimus-therapy. Our findings help stratifying patients who will benefit most from this therapy and avoid toxicities in patients without potential benefits for this therapy.
Gesehen am 24.02.2021